Outcomes of Renal Function in Cardiogenic Shock Patients With or Without Mechanical Circulatory Support - Upadhyaya, Vandan D. (J Clin Med Res, 2021)
BACKGROUND: The objective of the study was to compare the renal outcomes in patients presenting with all-cause cardiogenic shock who were supported by either Impella devices (Abiomed, Danvers, MA), intra-aortic balloon pump (IABP), or vasopressors alone. Outcomes of cardiogenic shock remain poor even with the advancement of early revascularization and circulatory supportive care. Percutaneous mechanical circulatory support (MCS) device has emerged as an effective strategy in protecting end organ function especially renal function during high risk percutaneous coronary intervention (PCI) and in patients with cardiogenic shock. Currently, comparative data amongst various MCS modalities and their association with improvement of renal function in cardiogenic shock patients have not been well characterized. METHODS: Data from New Jersey Cardiac Catheterization Data registry of cardiogenic shock patients from a single tertiary care institution that underwent cardiac catheterization and the modality used to treat were obtained, either with Impella devices, IABP, or treatment with vasopressors alone. Retrospective chart review was conducted to assess the incidence of acute kidney injury (AKI) on patients with cardiogenic shock prior to and after cardiac catheterization and renal function was evaluated over the course of 96 h after cardiac catheterization. Statistical analysis was performed to ascertain significant difference in creatinine and estimated glomerular filtration rate (eGFR) in patients who received Impella devices, IABP, or were treated with vasopressors alone. RESULTS: A total of 61 all-cause cardiogenic shock patients met the inclusion and exclusion criteria and were included in the study with 19 receiving IABPs, 15 receiving Impella devices, and 27 treated with vasopressors alone. Baseline characteristics among these three groups did not show any statistically significant difference. A total of 29 cardiogenic shock patients had experienced AKI prior to cardiac catheterization in which those receiving Impella devices showed statistically significant decrease in creatinine and increase in eGFR at 72 and 96 h (P < 0.05) compared to baseline. Within the same cohort, Impella group showed statistically significant lower creatinine at 96 h when compared to IABP. Patients that experienced AKI after cardiac catheterization did not show any statistically significant changes in renal function regardless of modality used. CONCLUSION: The results of our study suggest that Impella devices improve renal function in all-cause cardiogenic shock patients who experience AKI prior to undergoing cardiac catheterization.